Réponse :
Explications étape par étape :
A=2/3 - 7/3×8 / 21
A = 2/3 - (7×8)/( 3×3×7) = 2/3 - 8/9
A = 6/9 - 8/9 = - 2/9
B=(3/4 - 5/6)×3 / 2
B = (9/12 - 10/12) × 3/2
B = - 1/12 × 3/2 = ((-1)× 3)/(12×2)
B= - 3/(3×4×2) = - 1/8
C= (24/15 + 35/24)×20 / 33
C =((3×8)/(3×5) + 35/24) × 20/33
C = (8/5 + 35/24) × 20/33
C = (192/120 + 175/120) × 20/33
C = (367/120) × 20/33
C = (367 × 20)/( 6 × 20× 33)
C= 367/198
D=5/6 - 5/4 / 1/2 + 23
D = 5/6 - 2 × 5/4 + 23
D = 5/6 - 5/2 + 23
D = 5/6 - 15/6 + 23
D = - 10/6 + 23
D = - 5/3 + 23
D = - 5/3 + 69/3
D= 64/3